(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The paper addresses the issues of Don Milani’s teaching that have influenced and still stimulate the spirit of active citizenship, the creation of learning contexts and educational relationships, focusing on the experience of the Coordination of Milan-Schools, both in its initial phase in the 1980s and in its subsequent development from 2000 to nowadays.